2020
DOI: 10.1021/acsaem.0c00582
|View full text |Cite
|
Sign up to set email alerts
|

Dry Pressing Neat Active Materials into Ultrahigh Mass Loading Sandwich Cathodes Enabled by Holey Graphene Scaffold

Abstract: High areal performance from high cathode mass loading is an essential requirement to bring battery chemistries beyond the lithium (Li) ion, such as lithium–sulfur (Li–S) or lithium–selenium (Li–Se), toward practical applications. These conversion chemistry cathodes have been typically prepared by using conventional slurry-based techniques widely used for Li ion battery electrodes, requiring the use of solvent and binder and multiple steps such as mixing, casting, drying, and collecting and proper disposing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Compared to Li-S batteries with similarly prepared hG/S cathodes (Lin et al, 2019), the observed capacity loss for Li-Se batteries was much more severe with much lower percentages of capacity retention. Similar capacity loss was also previously observed for ultrahigh Se mass loading electrodes with a layered architectural configuration (Plaza-Rivera et al, 2020). Nevertheless, data of subsequent cycles 51-100 from the same cells of Figure 4D are shown in Supplementary Figure S2.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Compared to Li-S batteries with similarly prepared hG/S cathodes (Lin et al, 2019), the observed capacity loss for Li-Se batteries was much more severe with much lower percentages of capacity retention. Similar capacity loss was also previously observed for ultrahigh Se mass loading electrodes with a layered architectural configuration (Plaza-Rivera et al, 2020). Nevertheless, data of subsequent cycles 51-100 from the same cells of Figure 4D are shown in Supplementary Figure S2.…”
Section: Resultssupporting
confidence: 84%
“…The dual discharge voltage plateaus were also observed at higher current densities. At the same J A , the charge reaction exhibited a single plateau at ∼2.2 V, suggesting that the intermediate steps in the reverse battery reaction were much less distinct, commonly observed in the charge reactions of Li-S and Li-Se batteries in general (Eftekhari, 2017;Lin et al, 2019;Plaza-Rivera et al, 2020).…”
Section: Resultsmentioning
confidence: 95%
“…Holey graphene (hG), also known as graphene nanomesh, is a structural derivative of graphene, formed by producing nanometer-sized holes (i.e., nanopores) using a variety of techniques such as electron or ion-beam bombardment, nanolithography, templated growth, liquid-phase oxidation, chemical activation, gaseous-phase etching, or guided etching with catalytic or reactive nanoparticles. Significant progress has been made recently by taking advantage of the unique dry compressibility of hG for high mass loading, high areal capacity electrodes in a variety of energy-storage applications, including supercapacitors, Li-ion batteries, , Li–S/selenium (Se) batteries, , and Li-oxygen (O 2 ) batteries. , These electrodes for liquid electrolyte batteries were all prepared under solvent-free and binder-free conditions in straightforward dry-pressing processes enabled by hG. The role for hG is not only as a conductive additive but also as a dry-pressable matrix and a scaffold/binder.…”
Section: Introductionmentioning
confidence: 99%
“…25 Meanwhile, electrolyte design is another applicable approach, and it has been signified as a simple 28 However, a high proportion of inert species, i.e., cosolvent, in the electrolyte increases the cell polarization and lowers the capacity. 29 Even if an inert cosolvent can prevent the elution of LiPSs at low Sloading levels, techniques to investigate the behavior at high Sloading levels, where high amounts of LiPSs are generated, are lacking. 26 Therefore, to address the challenges arising due to the generation of high amounts of LiPSs and the resulting electrolyte viscosity in Li−S batteries with high S-loading levels, an electrolyte design that can stabilize the electrode and electrolyte interface is in high demand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Gu et al incorporated 1,3-(1,1,2,2-tetrafluoroethoxy)­propane (FDE), wherein LiPSs had poor solubility, in a DOL/DME ratio of 4:1 to suppress LiPS dissolution and improve cell performance . However, a high proportion of inert species, i.e., cosolvent, in the electrolyte increases the cell polarization and lowers the capacity . Even if an inert cosolvent can prevent the elution of LiPSs at low S-loading levels, techniques to investigate the behavior at high S-loading levels, where high amounts of LiPSs are generated, are lacking .…”
Section: Introductionmentioning
confidence: 99%